2005
DOI: 10.1016/j.cemconres.2004.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural analysis of recycled aggregate concrete produced from two-stage mixing approach

Abstract: Owing to the shortage of space for land reclamation in Hong Kong, it is difficult to dispose of tons of masonry waste generated daily from construction activities. Adoption of recycled aggregate from concrete waste thus becomes a burning issue. The Hong Kong SAR Government has set up a recycling plant in Tuen Mun Area 38 aiming at turning concrete waste into recycled aggregate with a practice note and specifications issued for controlling the quality of recycled aggregate. However, the use of recycled aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
329
0
46

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 788 publications
(381 citation statements)
references
References 12 publications
6
329
0
46
Order By: Relevance
“…For that reason, recycling CDW as a new aggregate source for concrete has received much more attention due to its feasibility, as well as its environmental and economic benefits [4]. Using recycled concrete aggregate (RCA) for concrete structures in many countries is still controversial and not easy to implement because of the lower qualities of RAC [5] and more complicated microstructure [6] such as containing large flat Ca(OH)2 crystals (CH crystal, about 20-25% of the volume of solids in the hydrated paste) which accumulated in the voids and in the cement paste [7]; a huge amount of pores and cracks; especially when it holds two interfacial transition zone (ITZ) systems including: new ITZ between RCA and new cement paste; old ITZ between old natural aggregate and old adhered mortar [6], which causes negative effects on performance of RAC [8]. Which is why, numerous studies have been conducted to evaluate and improve the mechanical and durability properties of RAC.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, recycling CDW as a new aggregate source for concrete has received much more attention due to its feasibility, as well as its environmental and economic benefits [4]. Using recycled concrete aggregate (RCA) for concrete structures in many countries is still controversial and not easy to implement because of the lower qualities of RAC [5] and more complicated microstructure [6] such as containing large flat Ca(OH)2 crystals (CH crystal, about 20-25% of the volume of solids in the hydrated paste) which accumulated in the voids and in the cement paste [7]; a huge amount of pores and cracks; especially when it holds two interfacial transition zone (ITZ) systems including: new ITZ between RCA and new cement paste; old ITZ between old natural aggregate and old adhered mortar [6], which causes negative effects on performance of RAC [8]. Which is why, numerous studies have been conducted to evaluate and improve the mechanical and durability properties of RAC.…”
Section: Introductionmentioning
confidence: 99%
“…(SCM or RCA) have different micro-structure. In the case of RCA concrete, it has greater porosity than conventional concretes (Gómez, 2002;Tam et al, 2005;Etxeberría et al, 2007). On the other hand, it has been demonstrated that concrete electric resistivity is associated with the microstructure of cement matrix (pores distribution) and with the corrosion rate of reinforced steel (Tumidajski et al, 1996;Tumidajski, 2005;Polder et al, 2000).…”
Section: As a Results Of The Significant Environmental Impact Causedmentioning
confidence: 99%
“…In RCA, the existing cementitious material on the transition zone is more porous, has small cracks and therefore the binding properties it affords are weak, critically influencing mechanical resistance. In addition, these pores and cracks tend to require more water, increasing the final amount of the liquid present at the transition zone between the new mixture and RCA [26]. Optical microscopy was used to identify the different transition zones.…”
Section: Tavares | C S Kazmierczakmentioning
confidence: 99%